2017
DOI: 10.14814/phy2.13127
|View full text |Cite
|
Sign up to set email alerts
|

A rat long‐lasting cystitis model induced by intravesical injection of hydrogen peroxide

Abstract: Novel longer lasting inflammatory bladder animal models are needed to better understand the pathophysiology of chronic cystitis. We previously developed a relatively long‐lasting mouse cystitis model by intravesical injection of hydrogen peroxide (H2O2). To further evaluate its pathophysiology, in this study, we established and analyzed a rat cystitis model. Under anesthesia, 1.5% H2O2 solution was introduced transurethrally into the bladder of female rats, and kept for 30 min. The H2O2 injection significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Multiple studies tried to explain the pathogenesis of FIC in cats by using animal models (Logadottir et al, 2014;Dogishi et al, 2017) like mice and rats or even by comparing it with human interstitial cystitis (IC) (Hauser et al, 2015). In fact, some of these studies revealed a part of the pathophysiology of the syndrome, yet still investigating the disease condition in naturally-occurring model of IC in cats may permit more accurate results than those obtained by acute models of inflammation/injury of the bladder in healthy animals.…”
Section: Research Articlementioning
confidence: 99%
“…Multiple studies tried to explain the pathogenesis of FIC in cats by using animal models (Logadottir et al, 2014;Dogishi et al, 2017) like mice and rats or even by comparing it with human interstitial cystitis (IC) (Hauser et al, 2015). In fact, some of these studies revealed a part of the pathophysiology of the syndrome, yet still investigating the disease condition in naturally-occurring model of IC in cats may permit more accurate results than those obtained by acute models of inflammation/injury of the bladder in healthy animals.…”
Section: Research Articlementioning
confidence: 99%
“…In addition to hyperactivity of bladder sensory neurons induced by long-lasting inflammation, bladder structural changes may affect the micturition function, leading to frequent urination. However, it is difficult to perform cystometric analysis in the present mouse cystitis model, although we could measure intercontraction interval and intravesical pressure in intravesical H 2 O 2 -induced rat cystitis model (Dogishi et al, 2017 ). Such technical problems by using genetically-modified mice limit to analyze the urodynamics in the mouse cystitis model.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the submucosa is exposed to irritants in the urine, which may activate TRPA1 expression on the bladder terminal of C-fibers. Alternatively, H 2 O 2 -induced acute inflammation of the bladder may be accompanied by bladder vascular hyperpermeability and infiltration of abundant inflammatory cells, including neutrophils, into the submucosa (Homan et al, 2013 ; Dogishi et al, 2017 ). Several lines of evidence suggest that ROS produced from infiltrated inflammatory cells contribute to bladder hyperactivity (Chien et al, 2003 ; Masuda et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been reported that a single intravesical administration of hydrogen peroxide (HP) induces relatively long-lasting bladder inflammation and bladder dysfunction for up to two weeks in mice and rats, and that changes in histology and urothelial permeability were similar to those observed in IC/BPS (ref. 9 , 10 ). We have also recently reported using the HP-induced cystitis rat model that liposome-based intravesical application of nerve growth factor (NGF) antisense reduced enhanced bladder pain sensitivity and bladder overactivity in association with a reduction in NGF expression in the bladder mucosa (ref.…”
Section: Introductionmentioning
confidence: 99%